Modernization of Future Educators’ Professional Training in the Context of Education for Sustainable Development - Tytarenko, Olha; Tytarenko, Valentyna; Tsyna, Andrii; Tytarenko, Valerii; Kulyk, Yevhen; Petrenko, Lesia (European Journal of Sustainable Development, 2025)
Modernization of professional training of future teacher education specialists is of particular relevance in the context of digitalization of the educational space, globalization of the labor market and growing demands on the professional competencies of teachers. Integration of innovative technologies, strengthening of practice-oriented learning and ensuring continuous professional development are key tasks of modern teacher education. This study aims to examine the existing conditions, prevailing trends, and future directions for updating the professional preparation of prospective teacher educators in both Ukraine and the global context. Methodologically, the research relied on comparing, systematizing, and synthesizing information from international reports, alongside analyzing scientific literature and regulatory acts. It also incorporated a secondary review of findings from global comparative assessments of teacher education quality. The research revealed that significant directions in updating teacher preparation include adopting a competency-based framework, enhancing digital skills, applying adaptive learning systems and VR/AR tools, and fostering stronger partnerships with employers as well as international educational organizations. Special emphasis is placed on developing intercultural competence and preparing educators to operate effectively in multilingual settings. It is proved that effective modernization requires an integrated approach that combines digital transformation, development of practical skills and creation of a system of continuous professional growth. . It is substantiated that teacher education for sustainable development is not only knowledge, but also the formation of a new culture of thinking and responsible behavior, which is a necessary condition for building a sustainable future. The practical value of the findings is reflected in their potential to inform the renewal of higher education curricula, enhance the substance and methodology of teacher preparation, shape a national strategy for advancing teacher education, and establish conditions for training competitive professionals capable of thriving in today’s digital learning environment. Keywords: professional training, digitalization of education, competency-based approach, teacher education, innovative technologies, intercultural competence, VR/AR, adaptive learning, international cooperation, pedagogical competencies, sustainable development education, environmental competence.